IMPLEMENTASI PERATURAN DAERAH NOMOR 7 TAHUN 2011 TENTANG PAJAK HIBURAN DI TINJAU DARI HUKUM ADMINISTRASI NEGARA (Studi Kota Medan) - Rinaldi Eka Saputra Aruan (Ilmu Hukum Prima (IHP), 2019)
Entertainment tax is one of the sources of regional income that is relied on by the city government for financing development. Medan City, which is one of the tourist cities where there are many entertainment venues such as malls, karaoke venues, movie theaters, nightclubs, art shows and so on. As for the problem in this study is the regulation of entertainment tax in Medan City, Implementation of Regional Regulation Number 7 of 2011 concerning Entertainment Tax Judging From State Administrative Law, Constraints in the Implementation of Regional Regulation Number 7 of 2011 Regarding Entertainment Tax Viewed From State Administrative Law. This study uses normative legal research methods. The normative legal research method studied is only material. Entertainment tax registration and taxpayer registration is the initial process before the object of entertainment tax is taxed, which is the process of collecting subject and tax object data which will later be used to conduct entertainment tax assessments and stipulations.